A Review of Desalination Potential in Greek Islands Using Renewable Energy Sources, a Life Cycle Assessment of Different Units - Karvounis, Panagiotis (European Journal of Sustainable Development, 2017)
The scarcity of water is a long-standing problem in Greek islands. The government, as a temporary solution adopted the transportation of water using tanker ships. This type of water is of low quality non-potable and in some cases inappropriate for any use. Apart from that water transportation increases the carbon footprint of the islands that it is already stained due to the big thermal power plants that feed the grid using fossil fuels (mainly diesel). Apart from the environmental issues the economic consequences are extremely high. The cost of transported water in Dodecanese and Cyclades reached a total of 73,5 million € from 2002 to 2010. The aim of this paper is to bring forward the proposed solutions for desalination of sea water using renewable energy sources, as Greek islands have a great wind and solar potential that is hard to find in any other place on Europe. A Life Cycle Assessment is been conducted between two different desalination technologies (RES and Diesel operating desalination) to fully understand the impact these units have to the environment. Keywords: Desalination, Renewable energy, Greek islands, carbon footprint, reverse osmosis, LCA